(untitled) (المجلة الدولية للبحوث العلمية, 2024)
This study examined the issue of the dominance of five European countries in the management of FIFA and its impact on fair representation and transparency in international sports decision-making. Several aspects were analyzed, including the lack of transparency and accountability, the loss of the mathematical scientific standard, the impact of political interference, and the lack of commitment to international human rights principles. The results showed that European hegemony marginalizes other countries and reduces their ability to participate effectively in decision-making processes within FIFA. There has also been a significant lack of transparency and accountability, which enhances Doubts about the integrity of decisions. In addition, non-compliance with scientific norms and significant political interference lead to unjustified decisions and favor political interests over sports justice. Finally, the lack of commitment to international human rights negatively affects the rights of peoples and players. The study recommended several recommendations to enhance transparency and accountability, redistribute power, adhere to scientific standards, reduce political interference, and promote human rights within FIFA. These recommendations aim to achieve balance and fairness in the management of world sport and ensure fair representation of all Member States, thus enhancing FIFA’s credibility and the confidence of Member States and the public in its decisions.